THE ROLE OF GREEN ACCOUNTING IN ENHANCING FINANCIAL TRANSPARENCY IN ISLAMIC FINANCIAL INSTITUTIONS - Wardiyah, Mia Lasmi; Dzikrayah, Fithri; Ponirah, Ade; Maulana, Izzul Haq Firman; Fiddienillah, Qheista Noor (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This study explores the role of green accounting in enhancing financial transparency within Islamic financial institutions. Green accounting, as an approach that integrates environmental responsibility into financial reporting, has gained attention for its potential to improve accountability and sustainability in finance. In Islamic finance, transparency is not only a regulatory requirement but also an ethical imperative aligned with Shariah principles. By conducting a literature review, this study synthesizes existing research on green accounting frameworks and their applicability in Islamic financial institutions. The findings suggest that adopting green accounting practices can bridge the gap between financial reporting and environmental stewardship, thus fostering greater stakeholder trust. Additionally, this approach aligns with the ethical and social objectives of Islamic finance, reinforcing the institutions' commitment to sustainable practices. This study provides insights for policymakers and financial managers aiming to integrate green accounting as a tool for transparency and sustainability. The research contributes to the discourse on sustainability in Islamic finance and highlights areas for future empirical investigation.